The development of production technology of wire rod from chromium-nickel-molibdenum steel grades with subsequent annealing spheroidization - S. V. Аudzeyey (Литьë и металлургия)
The peculiarity of the rod of chromium-nickel-molybdenum steel grades, used in the production of fasteners and automotive components by cold forming, are the high requirements for the quality of the surface, microstructure and physical and mechanical properties.In the process of development of production technology were developed and implemented measures to minimize the identified design features of heat treatment furnaces, and developed methods for obtaining the most optimal primary hot-rolled metal microstructure for further spheroidizing annealingIn industrial conditions OJSC «BSW – Management Company of Holding «BMC» was mastered the most optimal regimes of heat treatment of wire rod from chromium-nickel-molybdenum steel grades, which required the consumer a full range of physical and mechanical properties of wire rod from steel grades 38ХНГМ, 40XH2MA and 41Х1 used further in the manufacture of fasteners and automotive components by cold forging.